Dissecting Aortic Aneurysm Type B. Review of the Literature and an Analysis of our Own Observations. The Modern View of the Management and Treatment - Kravchenko, I. M.; Zhekov, I. I.; Perepeluk, A. I.; Osadovska, I. A.; Khyzhnyak, K. A.; Zinchenko, H. A.; Vayda, V. V. (Ukrainian Journal of Cardiovascular Surgery, 2016)
Despite considerable progress in diagnosis and treatment of patients with type B dissecting aneurysm of the aorta, mortality and morbidity levels are still significant. The distal dissection begins below the left subclavian artery, aorta extends downward and generally reaches the bifurcation of the abdominal aorta, occurs in about 20%.